TEST METHODS USED TO DETECT BREAST CANCER IN THE EARLY STAGES - Ruziyeva Shahlo Durdiqulovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article describes the examination methods used to detect breast cancer. The description of the most widely used instrumental inspection tools is given below.